Sezioni specializzate in materia di impresa e sezioni ordinarie: la sospensione scongiurata - Michelle Vanzetti (Il Diritto degli Affari, 2019)
This paper addresses the topic of the qualification of the relationship between an ordinary division and a division specializing in commercial matters, when placed in the same court, in the light of the well-known judgment of the Supreme Court No 19882/2019, to which it adheres, also offering an alternative solution.